Interrelationships of work-family conflict, spousal and organizational social support with psychological well-being among employees of public sector in Malaysia - Zakaria, Noorfadhila (2021)
Conflicts that occur due to the overlap between work and family matters are important topics in today’s organizational context. Work-family conflict can be defined as a form of role conflict where the demands of work and family cannot be aligned in several ways. Several previous studies have mentioned that work-family conflict negatively affects individuals. For example, emotional fatigue can lead to stress and disturb the psychological well-being of a person. From that perspective, social support can help to reduce the stressful experience caused by work-family conflict and improve psychological well-being. There are two elements of social support originating from (1) work domain support (organization, supervisor and co-workers) and (2) non-work domain supports (spouse, family members and friends). However, the limited numbers of studies focusing on the relationship between three variable factors, namely work-family conflict, spousal and organizational social support, and public sector employees’ psychological well-being especially in Malaysia has led to the establishment of this study. Two moderators of spousal and organizational social support were chosen as the focused subjects of this study due to their substantial effect. For this quantitative study, there were 400 respondents purposively selected using multi-stage sampling techniques. Self-administered questionnaire was used to collect data using four valid and reliable instruments, namely Work-to-Family Scale by Netmeyer, Boles, and McMurrian (1996), Family Support Inventory developed by King, Mattimore, King, and Adams (1995), Perceived Organizational Support scale, (University of Delaware, 1984), and Ryff Psychological Well-being scale by Ryff & Keyes, (1995). The study concluded that work-family conflict demonstrated a negative relationship, whereas spousal and organizational support showed positive associations with psychological well-being. Of all the three variables, organizational support was found to be the most significant factor to predict. psychological well-being among the employees of the public sector. It was also found that spousal and organizational support significantly moderate the relationship between work-family conflict and psychological well-being. This study's findings have practical implications for managers and leaders, implying that they must not only inspire and foster a healthy, friendly environment that will motivate employees to apply their energy and reach their full potential, thereby increasing psychological well-being, but also alleviate work-family conflict.